The strengths and pitfalls of Edmodo to Indonesian EFL learners: Student and teachers’ voices - Safriyani, Rizka; Khasanah, Siti Uswatun (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The Covid-19 pandemic impacted Indonesia's education system to change the teaching and learning activities rapidly. Edmodo is one of the Learning Management System (LMS) platforms widely used for English teaching and learning in Indonesia. Previous studies about Edmodo focus on the positive impact of Edmodo on the student's competence and performance. However, few studies discuss the pitfalls of Edmodo in EFL settings. A survey design was employed through the administration of the questionnaire. This survey research aims to investigate the strengths and the pitfalls of Edmodo to Indonesian EFL learners, particularly in the university context. Fifteen university students and ten lecturers were involved in the survey. The study results indicate that students and teachers have the same opinion about the strengths of Edmodo in terms of practicality and efficiency. However, a different opinion occurs on the use of Edmodo to complement face-to-face activity. Some teachers agree that Edmodo could not facilitate collaborative learning, but some lecturers said it was possible to do collaborative learning. Furthermore, students and teachers stated that the weaknesses of Edmodo need a good internet connection, especially for the quiz. This research, therefore, contributes some empirical insights into the use of Edmodo in English language teaching.